1998
DOI: 10.1006/dbio.1998.8946
|View full text |Cite
|
Sign up to set email alerts
|

Morphogenesis of Digits in the Avian Limb Is Controlled by FGFs, TGFβs, and Noggin through BMP Signaling

Abstract: In the final stages of limb morphogenesis, autopodial cells leaving the progress zone differentiate into cartilage or undergo apoptotic cell death, depending on whether they are incorporated into the digital rays or interdigital spaces. Most evidence indicates that these two opposite fates of the autopodial mesoderm are controlled by BMP signaling. However, the molecular basis for these two distinct actions of BMPs, including the receptors involved in the process, is controversial. In this study we have addres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
160
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(168 citation statements)
references
References 35 publications
7
160
0
1
Order By: Relevance
“…In a similar mechanism, FGF signaling was shown to suppress noggin expression in cranial sutures (50), thus explaining the premature fusion of cranial suture in individuals with activating mutations of FGF receptors 1 and 2. Experiments of chicken limb development have also shown that the application of FGF bound to beads can suppress noggin expression (51). These results highlight the interplay of BMP and FGF signaling that regulates both the osteoblast and chondrocyte lineage to shape both endochondral and membranous bones.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…In a similar mechanism, FGF signaling was shown to suppress noggin expression in cranial sutures (50), thus explaining the premature fusion of cranial suture in individuals with activating mutations of FGF receptors 1 and 2. Experiments of chicken limb development have also shown that the application of FGF bound to beads can suppress noggin expression (51). These results highlight the interplay of BMP and FGF signaling that regulates both the osteoblast and chondrocyte lineage to shape both endochondral and membranous bones.…”
Section: Discussionmentioning
confidence: 77%
“…Unregulated FGF signaling as in mice or humans with constitutively active FGF receptors may cause excessive inhibition of noggin expression and consequently develop abnormal digits or extremities. Noggin is widely expressed in condensing chondroblast mesenchyme and at the site of presumptive or developing joints (51). Therefore, local antagonism of BMP signaling by noggin may regulate the formation of joints and the shape of developing bone elements.…”
Section: Discussionmentioning
confidence: 99%
“…Cells within the medial layer express BMP-2 and subsequently undergo cell death, thereby forming the joint cavity, whereas the remaining outer layers will give rise to the articular cartilage (reviewed in Pacifici et al 2005). During joint formation, noggin is expressed within the intermedial layer of the interzone (Brunet et al 1998;Capdevila and Johnson 1998;Merino et al 1998;Goumans and Mummery 2000;Pizette and Niswander 2000;Seemann et al 2005;Lorda-Diez et al 2013), where it counteracts the effect of GDF-5, the key molecule required for defining the future joint interzone within the unpatterned digital ray. Loss of GDF-5 function leads to abnormal joint development with complete or partial fusion of consecutive skeletal elements and structural changes in autopods, along with other skeletal defects, whereas loss of noggin activity results in failure to initiate joint formation and thus symphalangism Kingsley 1996, 1999;Brunet et al 1998).…”
Section: Roles Of Tgf-b and Bmp Signaling In Limb Formation And Digitmentioning
confidence: 99%
“…Bmps are expressed mainly in the interdigital mesenchyme and the perichondrium whereas their receptors, in particular BmpR1b, are expressed in the condensing chondrocytes. Chondrogenesis in the limb is dependent on BMP signaling, since its inhibition in the chicken limb by implantation of Noggin beads, or retroviral overexpression of dominant-negative BMP receptors, equally interfere with chondrogenesis (Zou et al, 1997;Merino et al, 1998). In the mouse ablation of both type I receptors (BmpR1a and BmpR1b) causes a severe generalized chondrodysplasia in which most skeletal elements that form through endochondroal ossification are absent or rudimentary (Yoon et al, 2005;Ovchinnikov et al, 2006).…”
Section: Condensation Of the Digit Anlagenmentioning
confidence: 99%